Age modifies the association between driver's body mass index and death following motor vehicle crashes. (3rd October 2018) - Dubois, Sacha; Mushquash, Aislin R.; Weaver, Bruce; Bédard, Michel
Abstract: Objective: We explored the association between body mass index (BMI) and the odds of a driver being fatally injured in a motor vehicle crash (MVC) after controlling for driver, crash, and vehicle factors known to independently contribute to injury severity. We hypothesized that BMI would be related to risk of fatal injury after controlling for other risk factors but that BMI would also interact with age. Method: We analyzed crashes involving 2 passenger type vehicles (1998–2015) from the Fatality Analysis Reporting System using binary logistic regression (with generalized estimating equations) to compute odds ratios and 95% confidence intervals of fatality by BMI status. Results: Our results indicate that BMI status confers varying levels of risk at different ages. For example, a very low BMI of 18 increased the odds of fatality (relative to BMI = 21.75) more at age 85 (adjusted odds ratio [aOR] = 1.17, 95% confidence interval [CI], 1.09, 1.26) than at age 25 (aOR = 1.03, 95% CI, 1.01, 1.06). Similarly, a very high BMI of 42.5 increased the odds of fatality (relative to BMI = 21.75) more at age 85 (aOR = 2.17, 95% CI, 1.64, 2.87) than at age 25 (aOR = 1.33, 95% CI, 1.21, 1.45). Conversely, a moderate BMI of 27.5 was protective for drivers aged 85 (aOR = 0.94, 95% CI, 0.88, 0.99) but had no effect for drivers aged 25 (aOR = 1.00, 95% CI, 0.98, 1.02). We also found that a higher BMI was associated with higher odds of wearing a seat belt improperly or not wearing one at all. Conclusion: The relationship between BMI and fatality risk needs to be considered by policymakers, public health officials, and vehicle manufacturers to ensure that vehicles are safe for all occupants regardless of their weight, size, or shape.